Hair Restoration Techniques - Shehan, Jennifer Nicole; Spiegel, Jeffrey Howard (Facial Plastic Surgery, 2023)
Hair restoration is an essential topic in the current management of facial plastic surgery concerns and queries. Advances in hair restoration include oral and topical medications and compounded preparations, injections including platelet-rich plasma, light therapy, and follicular unit extraction methods. This article provides a review of current techniques.
Keywords: hair restoration; nonsurgical management; surgical management; follicular unit transplantation